2014
DOI: 10.24156/jikk.2014.7.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Nilai Dan Tipe Konsumen Rumah Tangga Dan Kaitannya Dengan Perilaku Pembelian Produk Makanan Kemasan

Abstract: AbstrakKarakteristik konsumen memegang peranan penting dalam menentukan keputusannya dalam sebuah proses pembelian, termasuk di dalamnya nilai yang diyakini dan tipe konsumen. Penelitian ini bertujuan untuk melihat pengaruh nilai dan tipe konsumen rumah tangga terhadap perilaku pembelian makanan kemasan di wilayah perkotaan dan perdesaan Bogor. Desain penelitian yang digunakan adalah cross sectional. Contoh penelitian melibatkan 80 rumah tangga yang mengonsumsi makanan kemasan yang dipilih secara random sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 7 publications
1
14
0
5
Order By: Relevance
“…Consumers who have education will be more responsive to information . This is in line with the results of research Ruwani et al (2014) the age and duration of mother's education affect food purchasing behaviour.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Consumers who have education will be more responsive to information . This is in line with the results of research Ruwani et al (2014) the age and duration of mother's education affect food purchasing behaviour.…”
Section: Discussionsupporting
confidence: 80%
“…This is following the research of Ruwani et al, (2014) that urban consumer types have higher purchasing behaviour than rural consumer types. The amount of money spent on buying fish depends on the type of fish selected, the number of fish purchasing, the price, and the frequency of buying fish in a month.…”
Section: Discussionmentioning
confidence: 99%
“…The label reading behavior on food products is done before buying the product Kumalasari and Sjafei 2012;Azman and Sahak 2014;Ruwani et al 2014). Respondents who paid attention to the food packaging label before buying food amounted to 61.2 percent ) with a factor influencing the respondent's attention to the food packaging label is the source of information.…”
Section: Label Reading Behavior On Food Productsmentioning
confidence: 99%
“…Ruwani (2014) found that about 97 percent of urban households buys dairy/processed products and about 90 percent buys snacks every month. This proves that the food packaging becomes one of the needs of consumers in urban as well as in rural areas.…”
Section: Label Reading Behavior Based On Research Sitesmentioning
confidence: 99%
“…According Ruwani, Retnaningsih, and Simanjuntak [4], the form of consumer attitudes toward a product greatly affect the buying behavior. Before purchasing the product, the consumer will evaluate from experience or knowledge so that low consumer knowledge and minimal information source can lead to wrong behavior in product selection and its long term manifestation to health problem.…”
Section: Introductionmentioning
confidence: 99%